กระบวนการจัดการเรียนรู้เพื่อพัฒนาคุณลักษณะของนักการเมือง บนฐานทฤษฎีการเรียนรู้เพื่อการเปลี่ยนแปลง - ยอดเณร, ปอรรัชม์; รักษ์พลเมือง, ชนิตา (Journal of Education Studies, Chulalongkorn University, 2014)
การวิจัยครั้งนี้เป็นการวิจัยเชิงคุณภาพโดยใช้เทคนิควิธีการศึกษาแบบผสมผสาน ประกอบด้วย การศึกษาเอกสาร การสำรวจความคิดเห็นของกลุ่มนักการเมืองและกลุ่มประชาชน การสัมภาษณ์เจาะ ลึกนักการเมืองและนักวิชาการ การวิจัยและพัฒนากระบวนการจัดการเรียนรู้ และการสนทนากลุ่ม ผู้ทรงคุณวุฒิมีวัตถุประสงค์เพื่อ ๑) วิเคราะห์คุณลักษณะที่พึงประสงค์ของนักการเมือง ๒) เพื่อพัฒนา กระบวนการจัดการเรียนรู้บนฐานทฤษฎีการเรียนรู้เพื่อการเปลี่ยนแปลง ๓) เพื่อนำเสนอกระบวนการ จัดการเรียนรู้เพื่อพัฒนาคุณลักษณะของนักการเมืองบนฐานทฤษฎีการเรียนรู้เพื่อการเปลี่ยนแปลง ผลการวิจัยพบว่า ๑) คุณลักษณะที่พึงประสงค์ของนักการเมืองแบ่งออกเป็น ๔ ด้าน คือ ด้าน จิตใจ ด้านความคิด ด้านพฤติกรรมและด้านความรู้ ๒) การวิจัยและพัฒนากระบวนการจัดการเรียนรู้ต้อง พัฒนาการเรียนรู้ ๔ ส่วน คือ การกระต้นุ การเรียนรู้ภายใน การเรียนร้เู ชิงกระบวนการกล่มุ การตระหนักถึง สังคมและส่วนรวม และการสร้างสรรค์แนวทางใหม่ ๓) กระบวนการจัดการเรียนร้เู พื่อพัฒนาคุณลักษณะ ของนักการเมืองประกอบด้วยการดำเนินการ ๗ ขั้นตอน คือ (๑) การกำหนดเป้าหมายการเรียนรู้ที่สัมพันธ์ กับคุณลักษณะที่พึงประสงค์ของนักการเมือง (๒) เนื้อหากิจกรรมต้องสอดคล้องกับเป้าหมาย (๓) การ ออกแบบกระบวนการจัดการเรียนรู้ให้เกิดประสบการณ์ใหม่ ใคร่ครวญ และแลกเปลี่ยนเชิงการเมือง (๔) การคัดเลือกกระบวนกร ที่มีประสบการณ์ทางการเมืองและการเรียนรู้เพื่อการเปลี่ยนแปลง (๕) การลงมือปฏิบัติต้องต่อเนื่องและยืดหยุ่น (๖) การสร้างบรรยากาศให้เท่าเทียมและเป็นประชาธิปไตย (๗) การสรุปและถอดบทเรียน เน้นการแลกเปลี่ยนและการรับฟังอย่างลึกซึ้ง This research has the following objectives: (1) to analyze the desirable characteristics of politicians, (2) to develop learning process management for politicians’ characteristics development based on Transformative Learning Theory, and (3) to propose a learning process management approach for developing characteristics of politicians based on the Transformative Learning Theory. The researcher employed mixed-method research which included document research,survey, in-depth interview with politicians and scholars, research and development and focus group discussions with experts. The result found that: 1) The desirable characteristics of politicians comprise four dimensions, namely, behavior, mind, intellect and knowledge characteristics. 2) In the research and development method, the process and activities for the experiment comprise four areas:, inner-self learning stimulation, group learning process, public and social awareness learning, and creation of innovative approaches 3)Regarding the presentation of the learning process management for developing politicians’ characteristics, it can be concluded that there are seven steps in the learning process management to develop politicians’ characteristics, namely: 1) setting a learning target that corresponds with the desirable characteristics of politicians; 2) def ining the content that ref lects the determined target; 3) designing learning process management whereby learners receive a new experience, and contemplate and exchange political experiences; 4) selecting a facilitator that has political experience and transformative learning; 5) implementing the process must be carried out continuously and with f lexibility; 6) creating a learning environment that promotes equality and democracy; 7) the summary and lesson learned must emphasize dialogue and sensible listening.